Surgical management of vascular anomalies in children at a tertiary care hospital in a resource-limited setting: a Tanzanian experience with 134 patients. (December 2015) - Chalya, Phillipo; Kayange, Neema; Rambau, Peter; Manyama, Mange; Gilyoma, Japhet
Abstract Background Vascular anomalies pose major diagnostic and therapeutic challenges among pediatricians and pediatric surgeons practicing in resource limited countries. There is paucity of published data regarding this subject in Tanzania and Bugando Medical Centre in particular. This study describes our experiences on the challenges and outcome of surgical management of childhood vascular anomalies in our environment. Methods Between January 2009 and December 2013, a prospective study on the surgical management of vascular anomalies was undertaken at Bugando Medical Centre. Results A total of 134 patients (M; F = 1:2.5) were studied. The median age at presentation was 6 years. Of the 134 patients, 101 (75.4 %) were diagnosed as having vascular tumors and 33 (24.6 %) had vascular malformations. The head and the neck were the most frequent anatomical site recorded as having a tumor (56.7 % of patients). Out of 134 patients, 129 (96.3 %) underwent surgical treatment. Failure to respond to non-operative treatment (86.8 %), huge disfiguring/obstructing mass (4.7 %), infection (3.1 %), ulceration (3.1 %) and hemorrhage (2.3 %) were indications for surgical intervention. Tumor excision and primary wound closure was the most common type of surgical procedure performed in 80.6 % of patients. Surgical site infection was the most frequent complications accounting for 33.8 % of cases. Mortality rate was 1.5 %. Tumor excision and primary wound closure gave better outcome compared with other surgical options (p < 0.001). Outcome of injection sclerotherapy in 3 (3.7 %) children, serial ligation of feeder vessels employed in 2 (1.6 %), and conservative treatment in 5 (3.7 %), were poor and required conversion to surgical excision. Despite low mortality rate recorded in this study, but ugly scar, 14 (20.6 %) and limb deformity, 6 (8.8 %) were problems. The overall result of surgical treatment at the end of follow up period was excellent in 108 (87.1 %) patients. Conclusion Surgical excision and primary wound closure gave good outcome which could be employed in complicated and vascular anomalies which failed to respond to other treatment in regions with limited resources.